Kirkemusik i stramme tøjler: Om alternatim-messer til Santa Barbara i Mantova - Woetmann Christoffersen, Peter (Danish Yearbook of Musicology, 2003)
The first part of this study discusses: the establishment of the ducal church la Basilica Palatina di Santa Barbara in Mantua during the years 1561-72; the cultural policy of duke Guglielmo Gonzaga, himself an accomplished composer who kept a tight rein on the polyphonic church music he ordered for his new church, and; the reformed repertory of cantus planus for Santa Barbara. The central part of this study takes a closer look at the only printed collection of music from Santa Barbara, Guilio Pellini’s Missae Dominicalis quinis vocibus diversorum auctorum (M. Tini: Venice 1592), which contains alternatim masses by Wert, Rovigo, Contino, Gastoldi, Striggio and Palestrina. They all conform perfectly to the duke’s wishes for his music (alternatim five-part imitative settings of the reformed liturgical songs – fugate continuamente), but also give an idea of how much room for personal expression this heavily regulated music allowed. Varied contrapuntal techniques, placement of dissonances and above all the timing of effects stand out as the most important means of expression in this ‘perfect’ church style (examples 3-8). The correspondence between Palestrina and the duke serves as a point of departure for a discussion of the relation between composer and patron. The last section of this study sketches a possible inspiration for the duke’s use of music from the church music of the imperial chapel during the reign of Maximilian I (Isaac’s Choralis constantinus appeared in print 1550-55), and the possible participation of the organ is also discussed. The Santa Barbara music is conservative in outlook, but may have been regarded – by the duke, as well as by his composers – as the embodiment of Catholic reforms after the Council of Trent, and as more closely related to the Latin Protestant church music (which was build on the great traditions from the period of Josquin Desprez and the imperial chapel) than to the Catholic contemporary tendency to emphasise text intelligibility.